2018
DOI: 10.1111/ppl.12675
|View full text |Cite
|
Sign up to set email alerts
|

Silicon affects seed development and leaf macrohair formation in Brachypodium distachyon

Abstract: Silicon (Si) has many beneficial effects in plants, especially for the survival from biotic and abiotic stresses. However, Si may negatively affect the quality of lignocellulosic biomass for bioenergy purposes. Despite many studies, the regulation of Si distribution and deposition in plants remains to be fully understood. Here, we have identified the Brachypodium distachyon mutant low-silicon 1 (Bdlsi1-1), with impaired channeling function of the Si influx transporter BdLSI1, resulting in a substantial reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 62 publications
(110 reference statements)
1
19
0
Order By: Relevance
“…The low - silicon 1 mutant ( Bdlsi1 - 1 ) plants used in this study carry a mutation in the Si influx transporter (BdLSI1), localized in the roots. The mutation severely hinders Si uptake and resulted in 93% reduction of the shoot Si content [ 29 ]. No phenotypic consequences were observed as the morphology and development of the Bdlsi1 - 1 plants were similar to the wild-type plants [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low - silicon 1 mutant ( Bdlsi1 - 1 ) plants used in this study carry a mutation in the Si influx transporter (BdLSI1), localized in the roots. The mutation severely hinders Si uptake and resulted in 93% reduction of the shoot Si content [ 29 ]. No phenotypic consequences were observed as the morphology and development of the Bdlsi1 - 1 plants were similar to the wild-type plants [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the Si uptake system and the levels of Si accumulation in shoot tissues are similar to those in barley, maize and wheat. Together these properties make B. distachyon a valuable tool for studies of biomass conversion [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Si supplementation has been shown to reduce the digestive efficiency through reduced cell rupture during insect digestion (Hunt et al, 2008). Previous work has found that Si is primarily deposited in leaf macrohairs in B. distachyon and that Si supplementation significantly increases both the number and length of these macrohairs (Głazowska, Murozuka, Persson, Castro, & Schjoerring, 2018). Our results indicate that this is an effective mechanical defence strategy against chewing herbivory in B. distachyon .…”
Section: Discussionmentioning
confidence: 98%
“…However, silicon may interact with polysaccharides, which consequently affect plant biomass processing in biorefineries (Perry & Lu, 1992;Kido et al, 2015). For biofuel production, there is a trade-off between soil amendment with silicon that can increase polysaccharide yield with a negative effect on the conversion of biomass into biofuels (Głazowska et al, 2018b). Silicon content in rice and maize can be modulated by changing the expression of silicon transporters (Ma et al, 2007;Mitani-Ueno et al, 2016;Bokor et al, 2017).…”
Section: Siliconmentioning
confidence: 99%
“…Silicon content in rice and maize can be modulated by changing the expression of silicon transporters (Ma et al, 2007;Mitani-Ueno et al, 2016;Bokor et al, 2017). The analysis of different silicon transporter mutants showed that silicon availability may impact the morphology and patterning of stem and leaf macrohairs (Głazowska et al, 2018b). The Bd low silicon 1 (Bdlsi1) mutant is impaired in silicon transporter function and has reduced silicon uptake, with 93% less silicon present in the shoot.…”
Section: Siliconmentioning
confidence: 99%